Dual MPPT Algorithm Implementation in Solar Charge Controller - P. Chandra Sekhar; B. Eswar Kumar; P. Sudheer (International Journal of Scientific Research in Science and Technology, 2024)
The implementation of a Dual Maximum Power Point Tracking (MPPT) algorithm in a solar charge controller is aimed at enhancing the efficiency of solar energy utilization. This algorithm optimizes power extraction from solar panels by dynamically adjusting the operating point to track the maximum power output under varying environmental conditions. By utilizing two MPPT trackers, the controller can efficiently handle scenarios with multiple peaks in the power-voltage curve, common in partially shaded or non-uniformly illuminated panels. This implementation involves real-time monitoring of panel voltages and currents, coupled with intelligent algorithms to swiftly respond to changes in irradiance levels. Through advanced control strategies, such as Perturbation and Observation (P&O) or Incremental Gradient (Incgrad), the system maximizes energy harvest, improving overall system performance and reliability.
Keywords: Solar Energy Charging Controller; MPPT; Synchronous Buck Converter; Battery Charger; Charge Controller